PENGARUH ROOM SERVICE TERHADAP BIAYA MAKANAN (FOOD COST) - Sri Kadaryati; Susetyowati Susetyowati; Lily Arsanti Lestari (Medika Respati : Jurnal Ilmiah Kesehatan, 2016)
Background : In addition to the therapy, food had economic value in the hospital finance. Food waste in hospitals was still high. Lack of food intake relate to the service system. Room service allowed the flexibility of load time and menu selection. The implementation of room service at hospitals could improve food quality, food intake, patient satisfaction, and reduce food costs.Objective : To study the influence of room service to plate waste costs in hospitalized patients.Method : This study was a pre-experimental static with 61 subjects in the inpatient unit of Class I and II RSUD Waled Kabupaten Cirebon. Subjects were divided into room service and conventional group. Food costs was calculated based ingredient in a menu portion. Plate waste was observed for 3 days with visual comstock 7 points methode, then converted to the plate waste costs. The difference in the plate waste costs was analyzed using Two Sample Independent T-test or Mann-Whitney Test.Result : Statistical analysis showed that there were significant differences in the plate waste costs of animal side dish, vegetable side dish, vegetable, extra of animal side dish, fruit, extra fruit, snack, and total food cost between room service and conventional (p < 0.05). The plate waste costs of staple food and drink didn’t differ significantly (p > 0.05).Conclusion : There was significant difference in the plate waste cost between the two groupsKeyword : food service, room service, food costs, plate waste costs